the solution of the equation (s, f) is (0.4, 0.3)
Step-by-step explanation:
12s + 15f =9.30 ...equation 1
4s + 10f=4.60 ...equation 2
Using elimination method:
To use this method, the variable we are to eliminate should have same coefficiet. SO eliminating s would mean mulitplying equation 2 by 3 so we would have same coefficient.
Multiply equation 2 by 3:
3(4s + 10f = 4.60)
12s + 30f = 13.8 ...equation 2
combining both equations:
12s + 15f =9.30 ...equation 1
12s + 30f = 13.8 ...equation 2
subtract equation 1 from 2:
12s - 12s + 30f - 15f = 13.8 - 9.3
0 + 15f = 4.5
15f = 4.5
divide both sides by 15:
15f/15 = 4.5/15
f = 0.3
substitute for f in any of the equation:
using equation1:
12s + 15(0. 3) = 9.3
12s + 4.5 = 9.3
12s = 9.3 - 4.5
12s = 4.8
divide both sides by 12:
12s/12 = 4.8/12
s = 0.4
Hence, the solution of the equation (s, f) is (0.4, 0.3) or (4/10, 3/10).